Economy and health of the productive population: the task of the development of regional sanatorium and health-resort organizations - Писаревський, Ілля Матвійович; Соколенко, Анна Сергіївна (Technology audit and production reserves, 2017)
The problem of maintaining the health of citizens as high-priority values of the human being and as a factor in ensuring efficient operation of enterprises and institutions is considered in the article. It is concluded that the economic effect of the use of human capital is closely dependent on the health of the working population, as well as regional policy should more actively promote system of health institutions including sanatorium and health-resort organizations. Characteristics and disease indicators of population and resources of health potential are analyzed for Kharkiv region. Assumptions to build a strategy for development of the regional health institutions are given. Conceptual functional of evaluation of human capital development in the region is given. The level of use and capacity of sanatorium and health-resort organizations of Kharkiv region and amount of their losses related to underuse and losses in regional GDP related to diseases of employees are determined.